2009
DOI: 10.1074/jbc.m109.005553
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the Fungal SC3 Hydrophobin into Functional Amyloid Fibrils Depends on Its Concentration and Is Promoted by Cell Wall Polysaccharides

Abstract: Class I hydrophobins function in fungal growth and development by self-assembling at hydrophobic-hydrophilic interfaces into amyloid-like fibrils. SC3 of the mushroom-forming fungus Schizophyllum commune is the best studied class I hydrophobin. This protein spontaneously adopts the amyloid state at the water-air interface. In contrast, SC3 is arrested in an intermediate conformation at the interface between water and a hydrophobic solid such as polytetrafluoroethylene (PTFE; Teflon). This finding prompted us t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 33 publications
0
39
1
Order By: Relevance
“…Thus, a particular class I or class II hydrophobin can be chosen depending on the requirements of the application. Biophysical and biochemical properties of hydrophobin films can be optimized by genetic engineering Lahtinen et al 2008;Joensuu et al 2010) or by adding surfactants (Morris et al 2011;Zhang et al 2011a, b, c;Tucker et al 2014), glycans (Scholtmeijer et al 2009), or other proteins (Danov et al 2014) …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, a particular class I or class II hydrophobin can be chosen depending on the requirements of the application. Biophysical and biochemical properties of hydrophobin films can be optimized by genetic engineering Lahtinen et al 2008;Joensuu et al 2010) or by adding surfactants (Morris et al 2011;Zhang et al 2011a, b, c;Tucker et al 2014), glycans (Scholtmeijer et al 2009), or other proteins (Danov et al 2014) …”
Section: Resultsmentioning
confidence: 99%
“…) and a long incubation time of 16 h. Finally, the conversion to the β-sheet 2 state is promoted by the presence of the cell wall polysaccharide schizophyllan (SPG) allowing conversion to the β-sheet 2 state at concentrations as low as 1 μg mL −1 (Scholtmeijer et al 2009). Maximal lowering of the water surface tension was reached after several hours with SC3 (Askolin et al 2006), while this occurred instantaneously in the case of ABH1 (Agaricus bisporus) (Paslay et al 2013).…”
Section: Conformational Changes During Self-assemblymentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, interaction between sugars and some class I hydrophobins has been studied. Scholtmeijer et al [17] have demonstrated that some polysaccharides promote rodlet formation of the class I hydrophobin SC3 at the interface between water and air or at a hydrophobic surface. Furthermore, it has been proved that the growth of amyloid fibrils, related to severe diseases, can be accelerated by glycosaminoglycans and proteoglycans [18,19].…”
Section: Introductionmentioning
confidence: 99%